(untitled) (JULACE: Journal of the University of Namibia Language Centre, 2018)
This paper describes the past and the present mourning practices and rituals of Aawambo. It examines traditional practices, which were adhered to in the ancient time, and the impact of modernization on the mourning practices of Aawambo. The paper also presents the responses of the Aawambo to the funeral rites in Oshiwambo society. Interdependent construal theory is used to identify the tenets of mutual obligations among Aawambo during the mourning rite. In addition westernisation theory is employed to gauge the impact of euro-western culture on the mourning practices and rituals of Aawambo. The data for this paper were collected through interviews, observation and documented texts. In the final analysis, the paper reveals that western cultures co-exist with Oshiwambo culture. It further reveals mourning period has become a conduit for class distinction associated with prestige, respect and economic status.